DIVERSITY, ABUNDANCE, STATUS AND ENDANGERED HABITATS OF AVIFAUNA IN SHEIKH BADIN NATIONAL PARK, DERA ISMAIL KHAN, KHYBER PAKHTUNKHWA, PAKISTAN - I. Ullah; WU Qing-Ming; Sun Xue-Ying; M. S. Khan; S. Ullah; T. U. Khan; R. M. Nawaz (Journal of Animal and Plant Sciences, 2020)
Bird species richness and diversity are the key factors that determine the health and productivity of an ecosystem. They have occupied a marvelous place, i.e., they play a vital role in the contribution of public consideration towards natural habitats and considered as barometers of an ecosystem. This study was carried out to determine the bird species diversity of the Sheikh Badin National Park, located in District Dera Ismail Khan, Khyber Pakhtunkhwa, Pakistan. For this purpose, bird watching surveys following line transect method were conducted from June 2018 to July 2019 in the study area. A total 3408 individuals (1260 migrants and 2148 residents) representing the 41 bird species were recorded during the surveys. Among the total, 18 species were migrants and 23 residents, belong to 11 Orders and 25 Families. Passeriformes was the dominant encompass of 19 species (9 native and 10 migrants) and 13 families. This national park harbored species richness was r = 41, Shannon-Weiner diversity index (H′ = 3.546), evenness (J′ 0.955) and Simpson’s Diversity (D = 0.966). The foraging guild results revealed that the granivore (2274) and insectivore (565) were the most abundant bird species. The major threats to the avifauna were illegal hunting, grazing and deforestation.
Keywords: National Park; Avifauna; Biodiversity; Habitat; Human Footprints; Hunting.